Smoke and mirrors : making sense of the WTO industrial tariff negotiations - Laird, Sam (UN New YorkUS, 2006)
Looks in some detail at the main implications for trade flows, tariff revenues, welfare and sectoral output for various countires and regions under proposals currently being considered in the WTO.